2013
DOI: 10.1144/sp381.22
|View full text |Cite
|
Sign up to set email alerts
|

Sedimentary processes in two different polar periglacial environments: Examples from Schirmacher Oasis and Larsemann Hills, East Antarctica

Abstract: Schirmacher Oasis and Bharati Promontory in Larsemann Hills of East Antarctica are currently ice-free coastal areas exposed in physiographically different polar periglacial environments. Schirmacher Oasis is bound by the presence of a vast stretch of ice shelf in the north and the polar ice sheet in the south. It exhibits well-developed patterned ground, abundant till deposition, block-fields, episodic development of curvilinear morainic ridges, extensive outwash plains and erratics. In contrast, the occurrenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…being characterized by further regression of the continental ice sheet, lowering of the lakes water tables and drying of the land. The main agents of the recent sediment transport within the oasis are surface runoff of the snow and ice meltwater (Asthana et al, 2013) which generate sandy surface deposits on the foothills and in depressions. Medium sand is the dominant grain size fraction.…”
Section: Study Areamentioning
confidence: 99%
“…being characterized by further regression of the continental ice sheet, lowering of the lakes water tables and drying of the land. The main agents of the recent sediment transport within the oasis are surface runoff of the snow and ice meltwater (Asthana et al, 2013) which generate sandy surface deposits on the foothills and in depressions. Medium sand is the dominant grain size fraction.…”
Section: Study Areamentioning
confidence: 99%
“…Several studies have been made on lake sediments from Schirmacher Oasis and Larsemann Hills in Antarctica to better understand the past changes in lacustrine environments (Govil et al, 2011(Govil et al, , 2012Shrivastava et al, 2012;Asthana et al, 2013). Phartiyal et al, (2011) have tried to reconstruct the evolution of the Schirmacher Oasis from 13 ka BP to the present.…”
Section: Palaeoclimatic Reconstruction Using Antarctic Lake Recordsmentioning
confidence: 99%
“…Field observations, granulometric analyses of sediment and morphological studies of selected quartz grains in Schirmacher Oasis and Larsemann Hills showed similar results, except for the extent and strength of glacial and glaciofluvial processes. Change in energy conditions is evident from the distribution pattern of sediments in both places (Asthana et al, 2013). Sedimentological properties of surface sediments from lakes of Schirmacher Oasis and Larsemann Hills helped to understand the sedimentary and glacial erosional processes taking place in the two regions.…”
Section: Palaeoclimatic Reconstruction Using Antarctic Lake Recordsmentioning
confidence: 99%
“…All the sediment samples were all poorly to very poorly sorted, fine-skewed to nearsymmetrical and platykurtic to leptokurtic in nature. Srivastava et al (2013) also performed mineralogical and geochemical studies on glacial sediments collected from different locations in Schirmacher Oasis. Mineralogically, the sediments are predominantly made up of quartz and feldspar in higher proportion, and a large variety of heavy minerals: zircon, tourmaline, rutile, garnet, hornblende, hypersthene, enstatite, kyanite, sillimanite, andalusite, zoisite, lawsonite, chlorite, spinel, topaz, and opaques.…”
Section: Studies On Surface Sediments and Sedimentwater Interface Fromentioning
confidence: 99%
“…The sediments underwent low degrees of chemical weathering (incipient to moderate) and the overall conclusion made through this study was that although there were minor differences amongst the sediments collected from different locations, they represented similar geochemical and mineralogical characteristics. Asthana et al (2013) studied the sedimentological properties of surface sediments from Schirmacher Oasis and Bharati Promontory, Larsemann Hills with an aim to understand the sedimentary and glacial processes taking place in the two regions. In addition to sedimentological data, scanning electron microscopic (SEM) observations on quartz grains were also made to strengthen the data.…”
Section: Studies On Surface Sediments and Sedimentwater Interface Fromentioning
confidence: 99%